PENGUJIAN MODEL PENERIMAAN TEKNOLOGI INTERNET PADA MAHASISWA - Petra Surya Mega Wijaya (Jurnal Riset Akuntansi dan Keuangan, 2005)
The rapid growth of investment in information technologt by orgoniza tions worldwide has made user acceptance an increasingly criticol technologt implementation and *orogr*rnt issues. User"icceptance has received fairly extensive attention from previous studies, particularly those involving dffirent technologies, user populations, and/or organizationalcontexts. The Technologt Acceptance Model @M is amongmost influential research models to determine information systems/information technologt use. The objective of thk study is to assess the TAM in world-wide-web usage. Data were collected from 127 undergraduate accounting students in Duta Wacana Christian (Jniversity-Yogyakarta and were tested using the structural equation modeling approach. The results of the study showed that, even though goodness of fit the model is not very well, there are significant coruelations among the perceived ease of use variable against perceived usefulness andattitude variable, perceived usefulness variable against attitude and behavior intention to use, attitude variable against behavior intention to use, and behavior intention to use variable against behavior to use. Implications of the future research areos ore discussed.Keywords: Perceived ease of use, perceived usefulness, attitude, behavior intention to use, behavior to use, TAM, SEM.